2022
DOI: 10.1186/s10033-022-00701-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Finite Element Modeling and Simulation of Soft Robots

Abstract: Soft robots have become important members of the robot community with many potential applications owing to their unique flexibility and security embedded at the material level. An increasing number of researchers are interested in their designing, manufacturing, modeling, and control. However, the dynamic simulation of soft robots is difficult owing to their infinite degrees of freedom and nonlinear characteristics that are associated with soft materials and flexible geometric structures. In this study, a nove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Future work will be devoted to extending the proposed energy-based controller to multiple models (and robots) [18]- [20], trajectory tracking problems, and experimental validation. Even if experimental validation remains a bottleneck for soft continuum robots, it was demonstrated that implementing actuation at the structure's tip enables good control in both regulation and tracking tasks [21].…”
Section: Discussionmentioning
confidence: 99%
“…Future work will be devoted to extending the proposed energy-based controller to multiple models (and robots) [18]- [20], trajectory tracking problems, and experimental validation. Even if experimental validation remains a bottleneck for soft continuum robots, it was demonstrated that implementing actuation at the structure's tip enables good control in both regulation and tracking tasks [21].…”
Section: Discussionmentioning
confidence: 99%
“…Future investigations could explore the use of different granular particles, adjusting the volume of granular bags, and selecting stronger DC motors for picking up heavier loads. In this scenario, numerical estimations [ 55 , 56 , 57 ] are useful to investigate the deformation. The artificial skin [ 58 , 59 , 60 ] can be covered outside the robot hand for sensing and friendly interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Its use has been widely implemented in soft robots [12,54]. In the case of pneumatic soft robots, the work of Ding [55]-which is, however, much smaller in size than PAUL-or Cangan [56], which uses previously presented SoPrA arm, stands out. The prob-lem they present, however, is the high computational cost required, which often makes their closed chain control unfeasible, unless reduced-order models are used [57].…”
Section: Control Of Soft Robotsmentioning
confidence: 99%